1996
DOI: 10.1093/oxfordjournals.eurheartj.a014721
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous balloon mitral valvotomy in mitral restenosis

Abstract: We conclude that percutaneous balloon mitral valvotomy can be performed safely and effectively in patients with mitral restenosis following surgical valvotomy; the beneficial acute outcome is sustained, as shown at intermediate-term follow-up and is similar to that of patients undergoing balloon mitral valvotomy as an initial procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 5 publications
6
14
0
Order By: Relevance
“…In our study, patients who had successful PBMV had lower Wilkin's score, and bilaterally fused commissural morphology (6,12), consistent with the findings of Turgeman, et al and Hung, et al who demonstrated that a more abnormal echocardiographic morphology predicted less symptomatic improvement and had a smaller post procedure valve area (9,13).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, patients who had successful PBMV had lower Wilkin's score, and bilaterally fused commissural morphology (6,12), consistent with the findings of Turgeman, et al and Hung, et al who demonstrated that a more abnormal echocardiographic morphology predicted less symptomatic improvement and had a smaller post procedure valve area (9,13).…”
Section: Discussionsupporting
confidence: 90%
“…Previous MV intervention was not associated with sub optimal outcomes, similar to the findings of Guptha et al who analysed 614 consecutive patients undergoing REDO PTMC including 8 patients (13.2%) with second mitral restenosis following prior surgical valvotomy (13). They found that percutaneous balloon mitral valvotomy can be performed safely and effectively in patients with mitral restenosis following surgical valvotomy.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In accordance with literature, there were more females in both study groups 3,12,18,20,22 and a greater percentage in the single balloon group in the present study.…”
supporting
confidence: 93%
“…The occurrence of severe mitral regurgitation during the procedure predicted events during long term evolution in other studies 11,12,13,19,22,32,35 and mitral regurgitation can be predicted by a specific echocardiographic score 36 . Mitral regurgitation before the valvuloplasty is a predictor of reduced event free survival 11 .…”
Section: Inoue Balloonmentioning
confidence: 79%